To Live Freely in This World : Sex Worker Activism in Africa - Mgbako, Chi (Book collections on Project MUSE., 2016)
"Sex worker activists throughout Africa are demanding an end to the criminalization of sex work and the recognition of their human rights to safe working conditions, health and justice services, and lives free from violence and discrimination. To Live Freely in This World is the first book to tell the story of the brave activists at the beating heart of the sex workers' rights movement in Africa, the newest and most vibrant face of the global sex workers' rights struggle. African sex worker activists are proving that communities facing human rights abuses are not bereft of agency. They're challenging politicians, religious fundamentalists, and anti-prostitution advocates; confronting the multiple stigmas that affect the diverse members of their communities; engaging in intersectional movement building with similarly marginalized groups; and participating in the larger global sex workers' rights struggle in order to determine their social and political fate. By locating this counter-narrative in Africa, To Live Freely in This World challenges disempowering and one-dimensional depictions of degraded Third World prostitutes and helps fill what has been a gaping hole in feminist scholarship regarding sex work in the African context. Based on original fieldwork in seven African countries, including Botswana, Kenya, Mauritius, Namibia, Nigeria, South Africa, and Uganda, Chi Adanna Mgbako draws on extensive interviews with over 160 African female and male (cisgender and transgender) sex worker activists, and weaves their voices and experiences into a fascinating, richly-detailed, and powerful examination of the history and continuing activism of this young movement"--Provided by publisher.